BLUE LIGHT EXPOSURE AND RETINAL HEALTH: MYTHS, EVIDENCE, AND THE ROLE OF BLUE LIGHT-BLOCKING INTERVENTIONS - Weronika Ossowska; Karolina Wojdat-Krupa; Wiktoria Ösztreicher; Paulina Lewaśkiewicz; Karol Sikora; Filip Lachowski (International Journal of Innovative Technologies in Social Science, 2025)
Aims: With the widespread use of digital devices and LED-based lighting, exposure to artificial blue light has significantly increased in recent years. This has raised concerns about potential retinal damage, disruption of circadian rhythms, and digital eye strain. At the same time, the market for blue light-blocking interventions, such as specialty eyewear and screen filters, has expanded rapidly. The aims of this review is to assess current scientific evidence on the biological effects of blue light on retinal health, evaluate the effectiveness of blue light-blocking strategies, and clarify common misconceptions.Methods: A narrative literature review was conducted using PubMed, Scopus, and Web of Science databases. Peer-reviewed articles published between 2010 and 2025 were included. The review focused on studies examining the retinal effects of blue light exposure, the pathophysiological mechanisms involved (including oxidative stress and phototoxicity), and clinical trials evaluating the use of blue light filters and digital ergonomics in reducing visual fatigue and sleep disruption.Results: Although experimental models suggest that high-intensity blue light may contribute to retinal oxidative stress, current clinical evidence does not support a direct link between typical screen exposure and long-term retinal damage. Blue light-blocking glasses show limited efficacy in reducing eye strain or improving sleep in the general population. Misconceptions about blue light toxicity persist, often driven by commercial claims rather than scientific validation.Conclusions: Blue light from screens poses minimal risk to retinal integrity under normal use conditions. Preventive strategies such as screen breaks, proper lighting, and digital ergonomics appear more effective than blue-blocking products. Health education efforts should focus on evidence-based practices rather than marketing-driven solutions.